TAWHID AND TOLERANCE: MUSLIM YOUTH ACTIVITIES RESPONSES TO THE INDONESIAN ULAMA COUNCIL’S PROHIBITION ON CHRISTMAS GREETINGS - Aprilinda M Harahap; Ziaulhaq Hidayat; Mohammad Fahmi Abdul Hamid (Peminat Ilmu Ushuluddin, 2025)
This study aimed to investigate Indonesian Ulema Council (MUI) fatwa on Christmas, particularly the prohibition of greeting Christians with “Merry Christmas.” It addressed two main questions, namely what is the content of MUI fatwa on Christmas, and how does the relationship between tawhid and tolerance manifest in Christmas greetings? To achieve this objective, a qualitative case study design was used. Data sources included MUI fatwa on Christmas and the perspectives of young Muslim activists on Christmas greetings. The results showed that MUI fatwa on Christmas and the prohibition of Christmas greetings were based on the 1981 and 2016 fatwas, further reinforced by sermons from North Sumatra and South Sulawesi MUI regarding Christmas greetings. MUI fatwa is derived from the Qur’an, Hadith, Usul Fiqh, and Ulama's opinions. The religious arguments referenced by MUI generally emphasize an attitude of hostility between Muslim and non-Muslim, while other normative sources that promote religious tolerance are not adequately referenced to provide a context for harmonious relations between Muslim and non-Muslim. Meanwhile, the perspective of young Muslim activists on the relationship between tawhid and Christmas greetings shows that there is no direct relationship between tawhid and Christmas greetings. However, the greetings can foster religious tolerance. MUI perspective on Christmas, particularly the prohibition of Christmas greetings, appears to be irrelevant to the context of Indonesian pluralistic society.